2016
DOI: 10.1038/ncomms12115
|View full text |Cite
|
Sign up to set email alerts
|

Genomics-informed isolation and characterization of a symbiotic Nanoarchaeota system from a terrestrial geothermal environment

Abstract: Biological features can be inferred, based on genomic data, for many microbial lineages that remain uncultured. However, cultivation is important for characterizing an organism's physiology and testing its genome-encoded potential. Here we use single-cell genomics to infer cultivation conditions for the isolation of an ectosymbiotic Nanoarchaeota (‘Nanopusillus acidilobi') and its host (Acidilobus, a crenarchaeote) from a terrestrial geothermal environment. The cells of ‘Nanopusillus' are among the smallest kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
154
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(159 citation statements)
references
References 56 publications
5
154
0
Order By: Relevance
“…The whole-cell proteome and the soluble proteins released into the medium were fragmented and analyzed by bottom-up, two-dimensional liquid chromatography-tandem mass spectrometry (2D-LC-MS/MS). A total of 1,628 proteins were detected, representing 70% of the predicted proteome (see Data Sets S1 and S6 in the supplemental material), which is similar to coverage that has been previously obtained on other organisms with reduced genomes (83,84). Considering that proteins containing multiple transmembrane domains are difficult to detect in tryptic digests (here we detected only 40% of the proteins predicted to contain more than 1 transmembrane domain) we conclude that a very large fraction of the D. oralis genetic potential (Ͼ80%) was expressed under the tested condition.…”
mentioning
confidence: 59%
“…The whole-cell proteome and the soluble proteins released into the medium were fragmented and analyzed by bottom-up, two-dimensional liquid chromatography-tandem mass spectrometry (2D-LC-MS/MS). A total of 1,628 proteins were detected, representing 70% of the predicted proteome (see Data Sets S1 and S6 in the supplemental material), which is similar to coverage that has been previously obtained on other organisms with reduced genomes (83,84). Considering that proteins containing multiple transmembrane domains are difficult to detect in tryptic digests (here we detected only 40% of the proteins predicted to contain more than 1 transmembrane domain) we conclude that a very large fraction of the D. oralis genetic potential (Ͼ80%) was expressed under the tested condition.…”
mentioning
confidence: 59%
“…In addition, ORF25-400 and ORF26-357 are homologous to each other and to the minor structural proteins conserved in all members of the family Rudiviridae (36) as well as in some members of the families Lipothrixviridae and Bicaudaviridae, all infecting members of the archaeal order Sulfolobales. Notably, whereas the N-terminal regions of ORF25-400 and ORF26-357 products showed highest similarity to the viral homologs, the central regions of the corresponding proteins were more similar to homologs encoded by "Candidatus Nanopusillus acidilobi," a symbiotic archaeon of the order Nanoarchaeota inhabiting terrestrial geothermal environments (37).…”
Section: Resultsmentioning
confidence: 99%
“…This first isolated geothermal nanoarchaeon, proposed as "Candidatus Nanopusillus acidilobi" represents the smallest cultured organism to date (100-300 nm cell size), and available cultures now allow experimentation to reveal its particular metabolism and adaptation features. Many more ultra-small bacteria and archaea with similar ectosymbiotic or ectoparasitic lifestyles might await discovery and identification of their hosts, something that -apart from single cell genomics -is only feasible by direct cultivation (Delafont et al 2015;He et al 2015;Wurch et al 2016). We conclude that genomic information of microbes derived from low diversity environments can often be obtained relatively easily and that individual genome reconstructions are often feasible (Figure 3).…”
Section: Extreme Environmentsmentioning
confidence: 97%
“…The nanoarchaeon's fragmented, extremely small genome lacked many essential biosynthetic pathways which indicated that the nanoarchaeon cannot live autonomously and hence depends on the presence of a crenarchaeal associate. Potential glycolysis and gluconeogenesis pathways, however, are retained in the nanoarchaeon, suggesting the use of peptides or complex sugars as energy source (Podar et al 2013;Wurch et al 2016). On this basis, Wurch et al (2016) established enrichment cultures containing yeast extract, casamino acids and sucrose or glycogen in anoxic Brock medium with low pH and 80-85 C and obtained stable communities with increasing relative abundance of nanoarchaeota, as monitored by qPCR.…”
Section: Extreme Environmentsmentioning
confidence: 99%
See 1 more Smart Citation